Glass composition, glass article, method of manufacturing glass article, and display device

Through the glass composition and tempering process of specific components, the problem of easy damage to glass products in portable electronic devices is solved, and high-strength, flexible glass products suitable for foldable display devices are prepared.

CN119219329APending Publication Date: 2024-12-31SAMSUNG DISPLAY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410846526.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-06-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing glass products are susceptible to external impact damage in portable electronic devices and are difficult to balance thinness and sufficient strength to meet folding needs.

Method used

Using a glass composition of a specific component ratio, including 60 mol% to 70 mol% SiO2, 5 mol% to 15 mol% Al2O3, 5 mol% to 15 mol% Na2O, 0 mol% to 5 mol% K2O and 0 mol% to 5 mol% Li2O, The ratio of 0.1≤Al2O3/(the sum of Na2O, K2O and Li2O)≤0.7 is met, and the strength and flexibility of glass products are improved through the tempering process.

Benefits of technology

Small-thickness glass products with excellent mechanical strength, surface strength and impact resistance are prepared, suitable for foldable display devices, with sufficient flexibility and strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219329A_ABST
    Figure CN119219329A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a glass composition, a glass article, a method of manufacturing the glass article, and a display device. The glass article includes the glass composition including 60 mol% to 70 mol% of SiO2, 5 mol% to 15 mol% of Al2O3, 5 mol% to 15 mol% of Na2O, greater than 0 mol% and equal to or less than 5 mol% of K2O, 5 mol% to 15 mol% of Li2O, and greater than 0 mol% and equal to or less than 5 mol% of MgO based on the total amount, and the glass composition satisfies the following relational expression (1): 0.1 < = Al2O3 / (the sum of Na2O, K2O, and Li2O) < = 0.7 relational expression (1), wherein Al2O3, Na2O, K2O, and Li2O in relational expression (1) indicate molar percentage (mol%) contents of Al2O3, Na2O, K2O, and Li2O, respectively, in the glass composition, and the glass article has a thickness of 100 [mu] m ([mu] m) or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to glass compositions, glass products, methods of manufacturing glass products, and display devices. Background Art

[0002] Glass products are widely used in electronic devices including display devices, building materials, etc. For example, glass products are applied to substrates of flat panel display devices such as liquid crystal display ("LCD") devices, organic light emitting display ("OLED") devices, or electrophoretic display devices, or to cover windows for protecting display devices.

[0003] As portable electronic devices such as smartphones and tablet personal computers ("PCs") increase, glass products applied to the portable electronic devices are often exposed to external impacts. Therefore, it is necessary to develop glass products that are thin and portable and can withstand external impacts.

[0004] Recently, a display device that can be folded for the convenience of users has been studied. A desired glass product applied to a foldable display device may have a thin thickness to relieve bending stress when folded, and at the same time may have sufficient strength to withstand external impact. Therefore, attempts have been made to improve the strength of thin glass products by changing the component ratio of the glass composition of the glass product and the conditions of the manufacturing process. Summary of the invention

[0005] Features of the present disclosure provide a glass composition having a novel composition ratio, a glass product made from the glass composition, a method of manufacturing the glass product, and a display device including the glass product.

[0006] However, the features of the present disclosure are not limited to the features set forth herein. The above and other features of the present disclosure will become more apparent to those of ordinary skill in the art to which the present disclosure pertains by referring to the detailed description of the present disclosure given below.

[0007] In an embodiment of the present disclosure, a glass article includes a glass composition comprising 60 mol% to 70 mol% SiO 2 , 5mol% to 15mol% Al 2 O 3 , 5 mol% to 15 mol% Na 2 O, greater than 0 mol% and equal to or less than 5 mol% K 2 O, 5 mol% to 15 mol% Li 2 O and greater than 0 mol % and equal to or less than 5 mol % of MgO, and the glass composition satisfies the following relational formula (1):

[0008] 0.1≤Al 2 O 3 / (Na 2 O.K 2 O and Li 2 O total) ≤ 0.7 Relationship (1)

[0009] Among them, Al in equation (1) 2 O 3 、Na 2 O.K 2 O and Li 2 O respectively indicate the Al content in the glass composition 2 O 3 、Na 2 O.K 2 O and Li 2 The glass article has a mole percent (mol%) content of O, and the glass article has a thickness of 100 micrometers (μm) or less.

[0010] In an embodiment, the glass article may have a thickness in a range of 20 μm to 100 μm.

[0011] In an embodiment, the thermal expansion coefficient of the glass article may be 90×10 -7 Per Kelvin (K -1 ) to 100×10 -7 K -1 within the range.

[0012] In an embodiment, the glass article may have a glass transition temperature in a range of 425 degrees Celsius (°C) to 525°C.

[0013] In an embodiment, the density of the glass article may be 2.38 g / cm3. 3 ) to 2.48g / cm 3 within the range.

[0014] In an embodiment, the glass article may have an elastic modulus in a range of 72 GPa to 82 GPa.

[0015] In an embodiment, the glass article may have a Poisson's ratio in the range of 0.20 to 0.22.

[0016] In an embodiment, the hardness of the glass article may be in the range of 5.50 GPa to 6.50 GPa.

[0017] In an embodiment, the fracture toughness of the glass article can be 0.75 MPa·m 0.5 ) to 0.85MPa·m 0.5 within the range.

[0018] In an embodiment, the brittleness of the glass article may be 7.0 μm. -0.5 Up to 8.0μm -0.5 within the range.

[0019] In an embodiment, the surface roughness of the glass article may be in a range of 0.2 nm to 0.45 nm.

[0020] In an embodiment, the glazing may be a foldable glazing.

[0021] In an embodiment of the present disclosure, a glass composition includes 60 mol% to 70 mol% of SiO based on the total amount. 2 , 5mol% to 15mol% Al 2 O 3 , 5 mol% to 15 mol% Na 2 O, greater than 0 mol% and equal to or less than 5 mol% K 2 O, 5 mol% to 15 mol% Li 2 O and greater than 0 mol % and equal to or less than 5 mol % of MgO, and the glass composition satisfies the following relational formula (1):

[0022] 0.1≤Al 2 O 3 / (Na 2 O.K 2 O and Li 2 O total) ≤ 0.7 Relationship (1)

[0023] Among them, Al in equation (1) 2 O 3 、Na 2 O.K 2 O and Li 2 O respectively indicate the Al content in the glass composition 2 O 3 、Na 2 O.K 2 O and Li 2 The molar percentage (mol%) content of O.

[0024] In an embodiment of the present disclosure, a display device includes a display panel having a plurality of pixels, a cover window disposed on the display panel, and an optically transparent bonding layer disposed between the display panel and the cover window, wherein the cover window includes a glass composition, the glass composition includes 60 mol % to 70 mol % of SiO based on the total amount. 2 , 5mol% to 15mol% Al 2 O3 , 5 mol% to 15 mol% Na 2 O, greater than 0 mol% and equal to or less than 5 mol% K 2 O, 5 mol% to 15 mol% Li 2 O and greater than 0 mol % and equal to or less than 5 mol % of MgO, and the glass composition satisfies the following relational formula (1):

[0025] 0.1≤Al 2 O 3 / (Na 2 O.K 2 O and Li 2 O total) ≤ 0.7 Relationship (1)

[0026] Among them, Al in equation (1) 2 O 3 、Na 2 O.K 2 O and Li 2 O respectively indicates Al in the glass composition 2 O 3 、Na 2 O.K 2 O and Li 2 The cover window has a mole percent (mol %) content of O, and the cover window has a thickness of 100 μm or less.

[0027] In an embodiment, the cover window may have a thickness of 20 μm to 100 μm.

[0028] In an embodiment, the cover window may have a 90×10 -7 K -1 Up to 100×10 -7 K -1 The coefficient of thermal expansion.

[0029] In an embodiment, the cover window may have a glass transition temperature of 425°C to 525°C.

[0030] In an embodiment, the cover window may have a thickness of 2.38 g / cm 3 Up to 2.48g / cm 3 density.

[0031] In an embodiment, the cover window may have an elastic modulus of 72 GPa to 82 GPa.

[0032] In an embodiment, the cover window may have a Poisson's ratio of 0.20 to 0.22.

[0033] In an embodiment, the cover window may have a hardness of 5.50 GPa to 6.50 GPa.

[0034] In an embodiment, the cover window may have a thermal conductivity of 0.75 MPa·m 0.5 To 0.85MPa·m 0.5 fracture toughness.

[0035] In an embodiment, the cover window may have a thickness of 7.0 μm. -0.5 Up to 8.0μm -0.5 brittleness.

[0036] In an embodiment, the cover window may have a surface roughness of 0.2 nm to 0.45 nm.

[0037] In an embodiment, the display device may be a foldable display device.

[0038] In an embodiment of the present disclosure, a method for manufacturing a glass product includes: forming a glass composition into a glass having a plate shape; cutting the glass; performing a first surface treatment on the glass; tempering the glass; and performing a second surface treatment on the glass, wherein the glass includes a glass composition including 60 mol % to 70 mol % of SiO based on the total amount. 2 , 5mol% to 15mol% Al 2 O 3 , 5 mol% to 15 mol% Na 2 O, greater than 0 mol% and equal to or less than 5 mol% K 2 O, 5 mol% to 15 mol% Li 2 O and greater than 0 mol % and equal to or less than 5 mol % of MgO, and the glass composition satisfies the following relational expression (1).

[0039] 0.1≤Al 2 O 3 / (Na 2 O.K 2 O and Li 2 O total) ≤ 0.7 Relationship (1)

[0040] Among them, Al in equation (1) 2 O 3 、Na 2 O.K 2 O and Li 2 O respectively indicates Al in the glass composition 2 O 3 、Na 2 O.K 2 O and Li 2The molar percentage (mol%) content of O.

[0041] In an embodiment, the first surface treatment may etch the surface of the glass at an etching rate of 1 micrometer / minute (μm / min) to 1.4 μm / min.

[0042] In an embodiment, the first surface treatment may etch the surface of the glass to a thickness of 0.8 μm to 1.2 μm.

[0043] In an embodiment, the second surface treatment may etch the surface of the glass at an etching rate of 1 μm / min to 1.4 μm / min.

[0044] In an embodiment, the second surface treatment may etch the surface of the glass to a thickness of 0.2 μm to 0.8 μm.

[0045] In an embodiment, after the second surface treatment, the surface roughness of the glass may be in the range of 0.2 nm to 0.4 nm.

[0046] The glass composition in the embodiment may have a novel composition ratio of components, and a glass product made of the glass composition may have excellent mechanical strength, surface strength and impact resistance, while having flexibility. In addition, a display device including the above glass product may have excellent flexibility and strength, to the extent that it can be applied to a foldable display device.

[0047] However, the effects of the present disclosure are not limited to the effects set forth herein. The above and other effects of the present disclosure will become more apparent to those of ordinary skill in the art to which the present disclosure belongs by referring to the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] These and / or other features will become apparent and more easily understood through the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0049] Figure 1 is a perspective view of an embodiment of a glass article;

[0050] Figure 2 is a perspective view showing an embodiment of a display device to which a glass product is applied in an unfolded state;

[0051] Figure 3 It is shown Figure 2 A perspective view of a display device in a folded state;

[0052] Figure 4 is a cross-sectional view showing an embodiment of applying a glass product as a cover window of a display device;

[0053] Figure 5is a cross-sectional view of an embodiment of a flat glass product;

[0054] Figure 6 It shows that according to Figure 5 A graph showing an embodiment of stress distribution of a glass article of an embodiment;

[0055] Figure 7 is a flow chart illustrating an embodiment of operations in a process for manufacturing a glass article;

[0056] Figure 8 It is shown Figure 7 A schematic diagram of a series of operations from a cutting operation to a second surface treatment operation;

[0057] Fig. 9 is a surface image of a glass product manufactured according to Comparative Example 1;

[0058] Fig.10 is a surface image of a glass product manufactured according to Example 1;

[0059] Fig.11 is a surface image of a glass product manufactured according to Example 2;

[0060] Fig.12 is a surface image of a glass product manufactured according to Example 3;

[0061] Fig.13 is a surface image of a glass product manufactured according to Example 4;

[0062] Fig.14 is a surface image of a glass product manufactured according to Example 5;

[0063] Fig.15 is a surface image of a glass product manufactured according to Example 6;

[0064] Fig.16 is a graph showing surface roughness according to etching thickness of glass articles manufactured according to Comparative Example 1 and Examples 1, 2, and 3;

[0065] Fig.17 is a graph showing the results of a pen drop test of a glass product according to Experimental Example 3;

[0066] Fig.18 schematically illustrates a pen drop test apparatus; and

[0067] Fig.19 is a graph showing the results of a pen drop test of glass articles according to Comparative Example 2 and Example 7. DETAILED DESCRIPTION

[0068] Embodiments of the present disclosure will now be described more fully below with reference to the accompanying drawings, in which preferred embodiments of the present invention are shown. However, the present invention may be implemented in different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that the present disclosure will be thorough and complete and will fully convey the scope of the present invention to those skilled in the art.

[0069] It will also be understood that when a layer or substrate is referred to as being “on” another layer or substrate, it can be directly on the other layer or substrate, or intervening layers may also be present. Throughout the specification, the same reference numerals refer to the same components.

[0070] It will be understood that although the terms "first", "second", etc. may be used herein to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element. For example, without departing from the teachings of the present invention, the first element discussed below may be referred to as the second element. Similarly, the second element may also be referred to as the first element.

[0071] Each of the multiple features of the various embodiments of the present disclosure can be combined in part or in whole or in combination with each other, and various interlocks and drives are technically possible. Each embodiment can be implemented independently of each other, or can be implemented together in association.

[0072] As used herein, "about" or "approximately" includes the stated value and means within an acceptable range of deviation of the particular value determined by one of ordinary skill in the art taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). The term "about" can mean within one or more standard deviations, or, for example, within ±30%, ±20%, ±10%, or ±5% of the stated value.

[0073] Hereinafter, embodiments will be described with reference to the accompanying drawings.

[0074] Figure 1 is a perspective view of an embodiment of a glass article.

[0075] Glass is used as a cover window for protecting a display, a substrate for a display panel, a substrate for a touch panel, an optical member such as a light guide plate, etc. in electronic devices including displays such as tablet personal computers ("PCs"), notebook PCs, smart phones, e-books, televisions, and PC monitors, and refrigerators and washing machines including display screens. Glass can also be used for cover glass of vehicle dashboards, cover glass of solar cells, building interior materials, and windows of buildings or houses.

[0076] It is desirable that the glass has great strength. In an embodiment, for example, it is desirable that the glass used for a window is thin to have a relatively high transmittance and a light weight, but it is desirable to be strong enough not to be easily broken by an external impact. A method such as chemical tempering or thermal tempering may be used to produce glass with increased strength. In an embodiment, in Figure 1 2 shows tempered glass having various shapes.

[0077] refer to Figure 1 In an embodiment, the glass article 100 may be in the shape of a flat sheet or plate. In other embodiments, the glass articles 101 to 103 may have a three-dimensional ("3D") shape including a bent portion. In an embodiment, for example, the glass article may have a flat portion with a bent edge (refer to glass article 101), may be substantially curved (refer to glass article 102), or may be folded (refer to glass article 103). In an alternative embodiment, the glass article 100 may be shaped as a flat sheet or plate, but may have flexibility such that it may be a foldable glass article that may be folded or bent. In addition, the glass article 100 may be stretched or rolled.

[0078] The glass articles 100 to 103 may have a rectangular planar shape. However, the glass articles 100 to 103 are not limited to the rectangular planar shape, and may also have various planar shapes, such as a rectangle with rounded corners, a square, a circle, and an ellipse. In the following embodiments, a flat plate having a rectangular planar shape will be described in the embodiments of the glass articles 100 to 103. However, it is clear that the present disclosure is not limited thereto. In an embodiment, the glass articles 100 to 103 may each include a first surface US, a second surface RS, and a side surface SS.

[0079] Figure 2 1 is a perspective view showing an example of an unfolded state of a display device to which a glass product is applied. Figure 3 It is shown Figure 2 A perspective view showing a folded state of the display device.

[0080] Reference Figure 2 and Figure 3 , the display device 500 in the embodiment may be a foldable display device. As will be described later, Figure 1 The glass article 100 may be applied as a cover window to the display device 500. The glass article 100 may have flexibility so that the glass article 100 may be folded.

[0081] exist Figure 2 and Figure 3, the first direction DR1 may be a direction parallel to one side of the display device 500 in a plan view, for example, a horizontal direction of the display device 500. The second direction DR2 may be a direction parallel to the other side of the display device 500 in contact with the upper side in a plan view, for example, a vertical direction of the display device 500. The third direction DR3 may be a thickness direction of the display device 500.

[0082] In an embodiment, the display device 500 may be a quadrilateral such as a rectangle in a plan view. In a plan view, the display device 500 may be shaped as a rectangle with vertical corners or a rectangle with rounded corners. In a plan view, the display device 500 may include two short sides arranged in a first direction DR1 and two long sides arranged in a second direction DR2.

[0083] The display device 500 includes a display area DA and a non-display area NDA. In a plan view, the shape of the display area DA may correspond to the shape of the display device 500. In an embodiment, for example, when the display device 500 is a quadrilateral (e.g., a rectangle) in a plan view, the display area DA may also be a quadrilateral (e.g., a rectangle).

[0084] The display area DA may include a plurality of pixels for displaying an image. The pixels may be arranged in a matrix form. However, the present disclosure is not limited thereto, and the pixels may be arranged in various other forms. In a plan view, each pixel may be shaped as a rectangle, a rhombus, or a square. However, the present disclosure is not limited thereto. In an embodiment, for example, each pixel may also be shaped as a quadrilateral, a circle, or an ellipse in addition to a rectangle, a rhombus, or a square in a plan view.

[0085] The non-display area NDA may not display an image because the non-display area NDA does not include pixels. The non-display area NDA may be disposed around the display area DA. The non-display area NDA may surround the display area DA. However, the present disclosure is not limited thereto. The display area DA may also be partially surrounded by the non-display area NDA.

[0086] In an embodiment, the display device 500 can maintain two states: a folded state and an unfolded state. Figure 3 As shown in , the display device 500 can be folded in an inward folding manner with the display area DA disposed inside. When the display device 500 is folded in the inward folding manner, portions of the upper surface of the display device 500 may face each other. In an alternative embodiment, the display device 500 can be folded in an outward folding manner with the display area DA disposed outside. When the display device 500 is folded in the outward folding manner, portions of the lower surface of the display device 500 may face each other.

[0087] In an embodiment, the display device 500 may be a foldable display device. In this specification, the term "foldable display device" is used to refer to a display device that can be folded, including not only a folded display device, but also a display device that can have both a folded state and an unfolded state. In addition, folding generally includes folding at an angle of about 180 degrees. However, the present disclosure is not limited thereto, and folding at an angle greater than or less than 180 degrees, such as folding at an angle greater than or equal to 90 degrees and less than 180 degrees or folding at an angle greater than or equal to 120 degrees and less than 180 degrees can also be understood as folding. In addition, when it is not an unfolded state, even an incomplete folded state can be referred to as a folded state. In an embodiment, for example, even a folded state at an angle of 90 degrees or less can be expressed as a folded state to distinguish it from an unfolded state, as long as the maximum folding angle is 90 degrees or more. The radius of curvature when folded can be 5 millimeters (mm) or less, preferably 1mm to 2mm or about 1.5mm. However, the present disclosure is not limited thereto.

[0088] In an embodiment, the display device 500 may include a folding area FDA, a first non-folding area NFA1, and a second non-folding area NFA2. The folding area FDA may be an area where the display device 500 is folded, and the first non-folding area NFA1 and the second non-folding area NFA2 may be areas where the display device 500 is not folded.

[0089] The first non-folding area NFA1 may be disposed on one side (eg, upper side) of the folding area FDA. The second non-folding area NFA2 may be disposed on the other side (eg, lower side) of the folding area FDA. The folding area FDA may be an area curved with a predetermined curvature.

[0090] In an embodiment, the folding area FDA of the display device 500 may be set at a predetermined position. In the display device 500, one folding area FDA or two or more folding areas FDA may be set at a predetermined position. In an embodiment, the folding area FDA may not be limited to a predetermined position in the display device 500, but may be freely set in various areas.

[0091] In an embodiment, the display device 500 may be foldable in the second direction DR2. Therefore, the length of the display device 500 in the second direction DR2 may be reduced to about half. Therefore, the user may easily carry the display device 500.

[0092] In an embodiment, the direction in which the display device 500 is folded is not limited to the second direction DR2. In an embodiment, for example, the display device 500 may also be folded in the first direction DR1. In this case, the length of the display device 500 in the first direction DR1 may be reduced to about half.

[0093] In the drawings, each of the display area DA and the non-display area NDA overlaps with the folding area FDA, the first non-folding area NFA1, and the second non-folding area NFA2. However, the present disclosure is not limited thereto. In an embodiment, for example, each of the display area DA and the non-display area NDA may overlap with at least one of the folding area FDA, the first non-folding area NFA1, and the second non-folding area NFA2.

[0094] Figure 4 is a cross-sectional view showing an embodiment of applying a glass product as a cover window of a display device.

[0095] refer to Figure 4 The display device 500 may include a display panel 200, a glass article 100 disposed on the display panel 200 and used as a cover window, and an optically transparent bonding layer 300 disposed between the display panel 200 and the glass article 100 to bond the display panel 200 and the glass article 100 together.

[0096] The display panel 200 may be, for example, a self-luminous display panel, such as an organic light emitting display (“OLED”) panel, an inorganic electroluminescent (“EL”) display panel, a quantum dot light emitting display (“QLED”) panel, a micro light emitting diode (“LED”) display panel, a nano LED display panel, a plasma display panel (“PDP”), a field emission display (“FED”) panel, or a cathode ray tube (“CRT”) display panel, or may be a light receiving display panel, such as a liquid crystal display (“LCD”) panel or an electrophoretic display (“EPD”) panel.

[0097] The display panel 200 may include a plurality of pixels PX, and may display an image using light emitted from each pixel PX. The display device 500 may further include a touch member (not shown). In an embodiment, the touch member may be built into the display panel 200. In an embodiment, for example, the touch member may be formed directly on the display member of the display panel 200 so that the display panel 200 itself may perform a touch function. In an embodiment, the touch member may be manufactured separately from the display panel 200, and then attached to the upper surface of the display panel 200 by an optically transparent bonding layer.

[0098] The glass article 100 is disposed on the display panel 200 to protect the display panel 200. The glass article 100 may be larger in size than the display panel 200. Therefore, the side surface SS of the glass article 100 may protrude outward from the side surface of the display panel 200, but the present disclosure is not limited to this case. The display device 500 may further include a printed layer (not shown) disposed in an edge portion of the glass article 100 on at least one surface of the glass article 100. The printed layer may prevent a frame area of ​​the display device 500 from being visible from the outside, and in some cases, may perform a decorative function.

[0099] The optically transparent bonding layer 300 is disposed between the display panel 200 and the glass article 100. The optically transparent bonding layer 300 fixes the glass article 100 on the display panel 200. The optically transparent bonding layer 300 may include an optically clear adhesive ("OCA") or an optically clear resin ("OCR").

[0100] The tempered glass article 100 described above will now be described in more detail.

[0101] Figure 5 is a cross-sectional view of an example of a flat glass product.

[0102] refer to Figure 5 The glass article 100 may include a first surface US, a second surface RS and a side surface SS (refer to Figure 1 ). The first surface US and the second surface RS of the flat-plate-shaped glass article 100 are main surfaces having relatively large areas, and the side surface SS is an outer surface connecting the first surface US and the second surface RS.

[0103] The first surface US and the second surface RS are opposite to each other in the thickness direction. When the glass article 100 is used to transmit light like a cover window of a display, light is usually incident on any one of the first surface US and the second surface RS, and then transmitted to the other of the first surface US and the second surface RS.

[0104] The thickness t of the glass article 100 is defined as the distance between the first surface US and the second surface RS. The thickness t of the glass article 100 may be, but is not limited to, in the range of 100 μm or less, preferably in the range of 20 μm to 100 μm. In an embodiment, the thickness t of the glass article 100 may be 80 μm or less. In another embodiment, the thickness t of the glass article 100 may be about 75 μm or less. In another embodiment, the thickness t of the glass article 100 may be about 70 μm or less. In another embodiment, the thickness t of the glass article 100 may be about 65 μm or less. In another embodiment, the thickness t of the glass article 100 may be about 60 μm or less. In another embodiment, the thickness t of the glass article 100 may be about 50 μm or less. In another embodiment, the thickness t of the glass article 100 may be about 30 μm or less. In an embodiment, the thickness t of the glass article 100 may be in the range of 20 μm to 50 μm, or may have a value of about 30 μm. The glass article 100 may have a uniform thickness t. However, the present disclosure is not limited thereto, and the glass article 100 may also have a different thickness t in each region.

[0105] The glass article 100 may be tempered to have a predetermined stress profile therein. Compared with the glass article 100 before tempering, the glass article 100 after tempering better prevents crack generation, crack propagation and breakage caused by external impact. The glass article 100 tempered by the tempering process may have various stresses in different regions. In an embodiment, for example, the compression regions CSR1 and CSR2 in which the compressive stress acts may be disposed near the surface of the glass article 100, i.e., near the first surface US and the second surface RS, and the tensile region CTR in which the tensile stress acts may be disposed inside the glass article 100. The stress values ​​of the boundaries DOC1 and DOC2 (hereinafter, also referred to as compression depths DOC1 and DOC2) between the compression regions CSR1 and CSR2 and the tensile region CTR may be zero. The compressive stress in one compression region CSR1 or CSR2 may have different stress values ​​depending on the position (i.e., the depth from the surface). In addition, the tensile region CTR may have different stress values ​​depending on the depth from the surface US or RS. In an embodiment, the first compression region CSR1 and the second compression region CSR2 may include a first transition point TP1 and a second transition point TP2 , respectively, at which a slope of the stress distribution changes abruptly.

[0106] In the glass article 100 , the positions of the compression regions CSR1 and CSR2 , the stress distribution within the compression regions CSR1 and CSR2 , the compression energy of the compression regions CSR1 and CSR2 , or the tension energy of the tension region CTR, etc. may have a significant effect on the mechanical properties of the glass article 100 , such as surface strength.

[0107] Figure 6 It shows that according to Figure 5 A graph showing stress distribution of a glass article of an embodiment of the present invention. Figure 6 In the graph of , the horizontal axis represents the thickness direction of the glass product. Figure 6 In the present specification, the magnitude of the compressive / tensile stress indicates the magnitude of the absolute value regardless of the sign of the value.

[0108] refer to Figure 6 Combined with Figure 5 , the glass article 100 includes a first compression region CSR1 extending (or expanding) from the first surface US to a first compression depth DOC1 and a second compression region CSR2 extending (or expanding) from the second surface RS to a second compression depth DOC2. The tensile region CTR is disposed between the first compression depth DOC1 and the second compression depth DOC2. In the overall stress distribution of the glass article 100, the regions on the two surfaces US and RS sides may be symmetrical to each other with respect to the center in the thickness t direction. Although in Figure 6 Although not shown in FIG. 1 , the compression region and the tension region may also be disposed between the opposing side surfaces of the glass article 100 in a similar manner.

[0109] The first compression region CSR1 and the second compression region CSR2 resist external impact to prevent cracks from being generated in the glass article 100 or the glass article 100 from breaking. The greater the maximum compressive stresses CS1 and CS2 of the first compression region CSR1 and the second compression region CSR2, the greater the strength of the glass article 100. Because external impact is generally transmitted through the surface of the glass article 100, it is advantageous in terms of durability to have the maximum compressive stresses CS1 and CS2 at the surface of the glass article 100. In this regard, the compressive stresses of the first compression region CSR1 and the second compression region CSR2 tend to be maximum at the surface and decrease toward the inside of the glass article 100.

[0110] The first compression depth DOC1 and the second compression depth DOC2 prevent cracks or grooves defined in the first surface US and the second surface RS from propagating to the tensile region CTR inside the glass article 100. The larger the first compression depth DOC1 and the second compression depth DOC2, the better the crack propagation can be prevented. The points corresponding to the first compression depth DOC1 and the second compression depth DOC2 correspond to the boundaries between the compression regions CSR1 and CSR2 and the tensile region CTR, and have a stress value of 0.

[0111] In the entire glass article 100, the tensile stress of the tensile region CTR may be balanced with the compressive stress of the compressive regions CSR1 and CSR2. That is, the total compressive stress (i.e., compressive energy) in the glass article 100 may be equal to the total tensile stress (i.e., tensile energy). The stress energy accumulated in one region having a predetermined width in the thickness t direction in the glass article 100 may be calculated by integrating the stress distribution. When the stress distribution in the glass article 100 having a thickness t is represented by a function f(x), the following equation may be established.

[0112]

[0113] As the magnitude of the tensile stress inside the glass article 100 increases, when the glass article 100 breaks, fragments may be violently ejected and may be crushed from inside the glass article 100. The maximum tensile stress that satisfies the brittleness standard of the glass article 100 may satisfy, but is not limited to, the following relationship.

[0114] CT1≤-38.7×ln(t)+48.2(2)

[0115] In some embodiments, the maximum tensile stress CT1 may be 100 megapascals (MPa) or less, or may be 85 MPa or less. A maximum tensile stress CT1 of 75 MPa or more may improve mechanical properties such as strength. In an embodiment, the maximum tensile stress CT1 may be, but is not limited to, 75 MPa to 85 MPa.

[0116] The maximum tensile stress CT1 of the glass article 100 may generally be disposed in a central portion of the glass article 100 in the thickness t direction. In an embodiment, for example, the maximum tensile stress CT1 of the glass article 100 may be disposed at a depth of 0.4t to 0.6t from the second surface RS, at a depth of 0.45t to 0.55t, or at a depth of about 0.5t.

[0117] Large compressive stress and compression depths DOC1 and DOC2 can be beneficial to enhancing the strength of the glass article 100. However, as the compression energy increases, the tensile energy also increases, thereby increasing the maximum tensile stress CT1. In order for the glass article 100 to meet the brittleness standard while having relatively high strength, the stress curve can be adjusted to increase the maximum compressive stresses CS1 and CS2 and the compression depths DOC1 and DOC2 and reduce the compression energy. To this end, the glass article 100 can be manufactured using a glass composition including predetermined components in predetermined proportions. Depending on the composition ratio of the components included in the glass composition, the manufactured glass article 100 can have excellent strength and at the same time can have flexible properties and physical properties that make it suitable for foldable display devices.

[0118] In an embodiment, the glass composition forming the glass article 100 may include 60 mol percent (mol %) to 70 mol % SiO based on the total amount of the glass composition. 2 , 5mol% to 15mol% Al 2 O 3 , 5 mol% to 15 mol% Na 2 O, greater than 0 mol% and equal to or less than 5 mol% K 2 O, 5 mol% to 15 mol% Li 2 O and greater than 0 mol % and equal to or less than 5 mol % of MgO.

[0119] Each component of the glass composition will be described in more detail as follows.

[0120] SiO 2 It can be used to form the frame of glass, increase chemical durability, and reduce the generation of cracks when scratches (indentations) are formed on the glass surface. SiO 2 It may be a network former oxide that forms a glass network, and is manufactured to include SiO 2 The glass article 100 may have a reduced thermal expansion coefficient and improved mechanical strength. In order to fully exert the above effects, SiO may be included in an amount of 60 mol% or more. 2 In order to exhibit sufficient meltability, SiO may be included in the glass composition in an amount of 70 mol % or less. 2 .

[0121] Al 2 O 3 Used to improve the breakability of glass. That is, when the glass breaks, Al 2 O 3 Can make the glass broken into a smaller number of pieces. 2 O 3Can be with SiO 2 The intermediate oxides that form bonds to form a network structure. 2 O 3 It can act as an active component to improve ion exchange performance during chemical tempering and increase surface compressive stress after tempering. When Al is included in an amount of 5 mol% or more 2 O 3 When 2 O 3 In order to maintain the acid resistance and solubility of the glass, 15 mol% or less of Al may be included. 2 O 3 .

[0122] Na 2 O is used to form surface compressive stress through ion exchange and improve the solubility of the glass. 2 O can form a network structure with SiO 2 The oxygen forms ionic bonds and 2 Non-bridging oxygen is formed in the network structure. The increase of non-bridging oxygen can improve the flexibility of the network structure and make the glass article 100 have physical properties that make it suitable for foldable display devices. When 5 mol% or more of Na 2 When O, Na 2 O can effectively play the above role. However, considering the acid resistance of the glass article 100, 15 mol% or less may be desirable.

[0123] K 2 O can replace Na with K to increase the compressive stress of the glass. 2 O can help realize the flexible glass article 100 by improving the folding reliability and bending reliability of the glass article. 2 When the content of O is greater than 0 mol%, K 2 O can effectively perform the functions described above. However, in terms of the fusibility of the glass article 100, it is preferred that K 2 The content of O is 5 mol% or less.

[0124] Li 2 O is used to form surface compressive stress through ion exchange and improve the solubility of the glass, similar to the Na described above. 2 O. Li 2 O can form a network structure with SiO 2 The oxygen forms ionic bonds and 2Non-bridging oxygen is formed in the network structure. The increase of non-bridging oxygen can improve the flexibility and shock absorption function of the network structure, and the glass article 100 can have its physical properties suitable for foldable display devices. In effectively performing the above-described functions, it is preferred that Li 2 The content of O is 5 mol% or more. However, in terms of heat resistance of the glass article 100, it may be preferred that Li 2 The content of O is 15 mol% or less.

[0125] MgO can improve the surface strength of glass and reduce the formation temperature of glass. MgO can be a 2 The network structure of the glass article 100 is modified to form a network modifier oxide of the network structure. MgO can reduce the refractive index of the glass and adjust the thermal expansion coefficient and elastic coefficient of the glass. When the content of MgO is greater than 0 mol%, MgO can effectively perform the functions described above. However, in terms of the solubility of the glass article 100, it is preferred that the content of MgO is 5 mol% or less.

[0126] In an embodiment, the glass composition may satisfy the following relational expression (1).

[0127] 0.1≤Al 2 O 3 / (Na 2 O.K 2 O and Li 2 O total) ≤ 0.7 Relationship (1)

[0128] Among them, Al in equation (1) 2 O 3 、Na 2 O.K 2 O and Li 2 O indicates Al 2 O 3 、Na 2 O.K 2 O and Li 2 O mole percentage (mol%) content. Value Al 2 O 3 / (Na 2 O.K 2 O and Li 2 The sum of the R ratios (R) may also be referred to as the R ratio.

[0129] As described above, the glass article 100 manufactured using the glass composition in the embodiment may have characteristics and physical properties that make it suitable for use in a foldable display device. In the embodiment, for example, the glass article 100 may have flexibility so that it can be folded and unfolded, and may have sufficient properties to make it suitable for use in a display device 500 (see Figure 4 )'s cover window strength and chemical properties.

[0130] By adding Na 2 O. Li 2 O and K 2 O, SiO included in the glass composition 2 and Al 2 O 3 The formed network structure can be transformed into a flexible network structure. 2 O. Li 2 O and K 2 The addition of O can make Na ions, Li ions and K ions form bonds with the network structure (for example, SiO 2 The oxygen between the bonds between the two groups (bonds between the two groups) forms an ionic bond, thereby increasing the non-bridging oxygen. The increase of the non-bridging oxygen in the network structure means that the bonds of the network structure are broken or opened. Therefore, the network structure of the glass can have flexibility. The glass composition may include Na in an amount of 5 mol% or more. 2 O, Li in an amount of 5 mol% or more 2 O and K in an amount greater than 0 mol% 2 O, so that the manufactured glass article 100 can have sufficient flexibility.

[0131] Since the glass composition contains a relatively excess of Na 2 O and Li 2 O, so the mechanical strength may be poor. To compensate for this, the glass composition may include Al 2 O 3 Here, Al 2 O 3 Content and Na 2 O content, Li 2 O content and K 2 The ratio of the sum of the O contents (i.e., R ratio) can be adjusted in the range of 0.1 to 0.7 according to the above relational formula (1). Therefore, mechanical strength can be added to the network structure. 2 O 3 Content and Na 2 O content, Li 2 O content and K 2 The ratio of the sum of the O contents (also referred to as R ratio) may be in the range of 0.1 to 0.7.

[0132] As Al in glass composition 2 O 3 Content and Na 2 O content, Li 2 O content and K 2 As the ratio of the sum of the O contents (R ratio) increases, the Al2 O 3 Can have SiO 2 The tetrahedral crystal structure formed by SiO 2 In the network structure formed, SiO 2 Can have a tetrahedral crystal structure [SiO 4 ], and when Na 2 O. Li 2 O and K 2 The sum of the O content and Al 2 O 3 When the content of Al 2 O 3 It can also have a tetrahedral crystal structure [AlO 4 ], and the mechanical strength can be improved. However, because the flexibility property is reduced as much as the mechanical strength is improved, in the embodiment shown, the Al 2 O 3 Compared with the content of 2 O. Li 2 O and K 2 O content.

[0133] When Al in the glass composition 2 O 3 Content and Na 2 O content, Li 2 O content and K 2 When the ratio of the sum of the O contents (R ratio) is 0.1 or more, Na 2 O content, Li 2 O content and K 2 O content can be increased, and increased Na 2 O. Li 2 O content and K 2 O can destroy SiO 2 The network structure increases the distance between atoms in the network structure. 2 A large amount of extra space is formed in the network structure, and thus the shock absorbing characteristics and flexibility can be improved.

[0134] In the embodiment, since Al in the glass composition 2 O 3 Content and Na 2 O content, Li 2 O content and K 2 The value of the ratio of the sum of the O contents (R ratio) is 0.1 to 0.7, so the glass article 100 may have flexibility, sufficient strength against external impact, and improved shock absorbing properties.

[0135] In an embodiment, the glass composition may include 65.16 mol % SiO 2 , 8.86 mol% Al 2 O 3 , 9.72 mol% Na 2 O, 3.2 mol% K 2 O, 10.08 mol% Li 2 O and 2.99 mol % MgO, and the R ratio according to the above relationship (1) can be 0.385.

[0136] When necessary, the glass composition may include, in addition to the components listed above, SnO 2 , Y 2 O 3 ,La 2 O 3 , Nb 2 O 5 、 2 O 5 and Gd 2 O 3 In addition, the glass composition may also include a trace amount of Sb 2 O 3 、CeO 2 and / or As 2 O 3 As a clarifying agent.

[0137] The glass composition having the above composition ratio and components can be molded into the shape of a flat glass using various methods known in the art. Once molded into the shape of a flat glass, the glass composition can be further processed to produce a glass product 100 that can be applied to the display device 500. However, the present disclosure is not limited thereto, and the glass composition may not be molded into the shape of a flat glass, but may be directly molded into a glass product 100 suitable for a product without an additional molding process.

[0138] A process of molding the glass composition into a flat glass shape and then processing into the glass article 100 will now be described.

[0139] Figure 7 is a flow chart illustrating an embodiment of operations in a process for manufacturing a glass article. Figure 8 It is shown Figure 7 Schematic diagram of a series of operations from a cutting operation to a second surface treatment operation.

[0140] refer to Figure 7 and Figure 8 , manufacturing glass products 100 (reference Figure 1) may include a molding operation (operation S1), a cutting operation (operation S2), a side polishing operation (operation S3), a first surface treatment operation (operation S4), a tempering operation (operation S5), and a second surface treatment operation (operation S6).

[0141] The molding operation (operation S1) may include preparing a glass composition and molding the glass composition. The glass composition may have the above-mentioned composition ratio and components, which will not be described in detail here. The glass composition may be molded into a flat glass shape by a method such as a float process, a fusion drawing process, or a slot drawing process.

[0142] The glass molded into a flat plate shape may be cut by a cutting operation (operation S2). The glass molded into a flat plate shape may have a size different from the size applied to the final glass product 100. In an embodiment, for example, the glass may be molded into a glass 10a of a mother substrate unit including a plurality of glass products in a state of a large-area substrate, and then may be cut into a plurality of units to produce a plurality of glass products. In an embodiment, for example, although the final glass product 100 has a size of about 6 inches, the glass may be molded into a size (e.g., 120 inches) several to hundreds of times the size of the final glass product 100, and then cut to produce 20 flat plate shapes at a time. This may improve process efficiency compared to when each glass product is molded separately. In addition, even when glass corresponding to the size of one glass product is molded, when the final glass product has various planar shapes, a desired shape may be formed by a cutting process.

[0143] The cutting of the glass 10 a of the mother substrate unit may be performed using a cutting blade 20 , a cutting wheel, a laser, or the like.

[0144] The cutting operation of the glass (operation S2) may be performed before the tempering operation of the glass (operation S5). The glass 10a corresponding to the mother substrate may also be tempered and then cut into the final glass product size. However, in this case, the cutting surface (e.g., the side surface) of the glass may not be tempered. Therefore, it is desirable to perform the tempering operation (operation S5) after completing the cutting operation (operation S2).

[0145] A pre-tempered polishing operation may be performed between a glass cutting operation (operation S2) and a glass tempering operation (operation S5). The pre-tempered polishing operation may include a side polishing operation (operation S3) and a first surface treatment operation (operation S4). In an embodiment, the side polishing operation (operation S3) may be performed before the first surface treatment operation (operation S4), but the order may be reversed.

[0146] The side polishing operation (operation S3) is an operation of polishing the side surface of the cut glass 10. In the side polishing operation (operation S3), the side surface of the cut glass 10 is polished to have a smooth surface. In addition, each side surface of the cut glass 10 can have a uniform surface by the side polishing operation (operation S3). More specifically, the cut glass 10 may include one or more cut surfaces. In some cut glasses 10, two of the four side surfaces may be cut surfaces. In some other cut glasses 10, three of the four side surfaces may be cut surfaces. In some other cut glasses 10, all four side surfaces may be cut surfaces. When the side surface is a cut surface, it may have a surface roughness different from the surface roughness of the uncut surface. In addition, even the cut surface may have a different surface roughness. Therefore, by polishing each side surface by the side polishing operation (operation S3), each side surface may have a uniform surface roughness, etc. In addition, when there are relatively small cracks on the side surface, they can be removed by the side polishing operation (operation S3).

[0147] The side polishing operation (operation S3) may be simultaneously performed on the plurality of cut glasses 10. That is, in a state where the plurality of cut glasses 10 are stacked, the stacked cut glasses 10 may be simultaneously polished.

[0148] The side polishing operation (operation S3) may be performed by a mechanical polishing method or a chemical mechanical polishing method using the polishing device 30. In an embodiment, two opposing side surfaces of the cut glass 10 may be polished simultaneously, and then another two opposing side surfaces may be polished simultaneously, but the present disclosure is not limited thereto.

[0149] The first surface treatment operation (operation S4) may heal the cut glass 10. In the first surface treatment operation (operation S4), the reduced strength of the glass surface may be improved by performing the first surface treatment on the cut glass 10. The first surface treatment operation (operation S4) may be performed by accommodating the cut glass 10 in a box and immersing the cut glass 10 in a repair solution 40. The repair solution 40 may be a solution including or consisting of fluoride ions. In an embodiment, the repair solution 40 may include, for example, at least one of hydrofluoric acid, sulfuric acid, hydrochloric acid, and ammonium fluoride or consist of at least one of hydrofluoric acid, sulfuric acid, hydrochloric acid, and ammonium fluoride.

[0150] In the first surface treatment operation (operation S4), the entire surface of the cut glass 10 can be etched by the repair solution 40. The etching of the cut glass 10 can be performed at an etching rate of 1 micrometer / minute (μm / min) to 1.4μm / min, and can be performed with an etching thickness of the cut glass 10 within a range of 0.8μm to 1.2μm from the surface of the cut glass 10. The etching rate can be controlled by adjusting the concentration of the repair solution 40. The surface of the cut glass 10 may affect the impact resistance in a state with fine cracks. In the illustrated embodiment, the impact resistance of the cut glass 10 can be improved by removing the fine cracks of the cut glass 10 by etching.

[0151] Subsequently, the cut glass 10 is strengthened (operation S5). The tempering operation of the glass (operation S5) may be performed once or multiple times. Below, the tempering operation of the glass (operation S5) is described as being performed three times as an example, but the present disclosure is not limited thereto, and the tempering operation of the glass (operation S5) may be performed once or twice.

[0152] The first tempering operation includes a first ion exchange process of immersing the cut glass 10 in a first molten salt. The first molten salt may include sodium nitrate (NaNO 3 ) and potassium nitrate (KNO 3 ) or sodium nitrate (NaNO 3 ) and potassium nitrate (KNO 3 ), the concentration of sodium (Na) ions in the cations in the molten salt may be 75 mol% to 25 mol%, and the concentration of potassium (K) ions may be 25 mol% to 75 mol%. The first ion exchange process may be performed at a temperature of about 385 degrees Celsius (°C) to 405°C for about 90 minutes to about 240 minutes.

[0153] In the first ion exchange process, lithium (Li) ions on the glass surface can be exchanged for sodium (Na) ions. When the glass including or consisting of lithium (Li) ions is immersed in a solution including sodium nitrate (NaNO 3 ) or sodium nitrate (NaNO 3 ) is exposed to sodium (Na) ions in a molten salt tempering tank composed of lithium (Li) ions or glass composed of lithium (Li) ions, and the lithium (Li) ions on the surface of the glass are discharged to the outside, and the sodium (Na) ions can replace them. Because the exchanged sodium (Na) ions have a larger ionic radius than lithium (Li) ions, compressive stress can be generated. As the amount of exchanged sodium (Na) ions increases, the compressive stress increases. As the first ion exchange process proceeds, lithium (Li) ions can be eluted from the inside of the glass, and the sodium (Na) ion content in the mixed molten salt generally decreases.

[0154] The second tempering operation includes a second ion exchange process of immersing the cut glass 10 that has undergone the first tempering operation in a second molten salt. The second molten salt may include sodium nitrate (NaNO 3 ) and potassium nitrate (KNO 3 ) or sodium nitrate (NaNO 3 ) and potassium nitrate (KNO 3 ), the content of sodium (Na) ions in the cations in the molten salt may be 5 mol% to 10 mol%, and the content of potassium (K) ions may be 90 mol% to 95 mol%. The second ion exchange process may be performed at a temperature of about 370° C. to 390° C. for about 30 minutes to about 120 minutes.

[0155] When the cut glass 10 including or consisting of sodium (Na) ions is immersed in a solution including potassium nitrate (KNO 3 ) and sodium nitrate (NaNO 3 ) or potassium nitrate (KNO 3 ) and sodium nitrate (NaNO 3 ) and exposed to potassium (K) ions, sodium (Na) ions in the glass are discharged to the outside, and potassium (K) ions can replace them. Since the exchanged potassium (K) ions have a larger ionic radius than the sodium (Na) ions, they generate compressive stress. The larger the amount of exchanged potassium (K) ions, the greater the compressive stress.

[0156] The third tempering operation includes a third ion exchange process of immersing the glass subjected to the second tempering operation in a third molten salt. The third molten salt includes potassium nitrate (KNO 3 ), and the concentration of potassium (K) ions in the cations in the molten salt may be 99.5 mol % to 100 mol %. The third ion exchange process may be performed at a temperature of about 370° C. to 390° C. for about 5 minutes to about 10 minutes.

[0157] Sodium (Na) ions inside the glass that are not exchanged in the ion exchange process of the second tempering operation may be exchanged for potassium (K) ions. The ion exchange process may be performed on the surface of the glass.

[0158] After the tempering operation (operation S5), a second surface treatment operation (operation S6) may be performed. In the second surface treatment operation (S6), similar to the first surface treatment operation (operation S4) described above, the reduced strength of the glass surface may be improved by performing a second surface treatment on the cut glass 10. The second surface treatment operation (operation S6) may be performed by accommodating the cut glass 10 in a box and immersing the cut glass 10 in a repair solution 40. The repair solution 40 may be a solution including or consisting of fluoride ions. In an embodiment, for example, the repair solution 40 may include at least one of hydrofluoric acid, sulfuric acid, hydrochloric acid, and ammonium fluoride or consist of at least one of hydrofluoric acid, sulfuric acid, hydrochloric acid, and ammonium fluoride.

[0159] In the second surface treatment operation (operation S6), the entire surface of the cut glass 10 may be etched by the repair solution 40. The etching of the cut glass 10 may be performed at an etching rate of 1 μm / min to 1.4 μm / min, and may be performed with an etching thickness of the cut glass 10 within a range of 0.2 μm to 0.8 μm from the surface of the cut glass 10. In the second surface treatment operation (operation S6), the impact resistance of the cut glass 10 may be improved by removing fine cracks of the cut glass 10 by etching. In the illustrated embodiment, the cut glass 10 may have a surface roughness by the first surface treatment operation (operation S4) and the second surface treatment operation (operation S6). The surface roughness of the cut glass 10 may be in the range of 0.2 nm to 0.45 nm, preferably in the range of 0.2 nm to 0.4 nm.

[0160] Although not shown in the figure, after the second surface treatment operation (operation S6), a shape machining process may be further performed as needed. Figure 1 When the 3D glass articles 101 to 103 shown in FIG. 1 are formed, a 3D machining process may be performed after the second surface treatment operation (operation S6 ) is completed.

[0161] The glass article 100 manufactured by the above method may have a component ratio similar to that of the glass composition. In an embodiment, for example, the glass article 100 may include 60 mol% to 70 mol% of SiO based on the total amount. 2 , 5mol% to 15mol% Al 2 O 3 , 5 mol% to 15 mol% Na 2 O, greater than 0 mol% and equal to or less than 5 mol% K 2 O, 5 mol% to 15 mol% Li 2O and greater than 0 mol % and equal to or less than 5 mol % of MgO. The glass composition used to manufacture the glass article 100 may satisfy the following relational expression (1).

[0162] 0.1≤Al 2 O 3 / (Na 2 O.K 2 O and Li 2 O total) ≤ 0.7 Relationship (1)

[0163] Among them, Al 2 O 3 、Na 2 O.K 2 O and Li 2 O is the mole percentage (mol%) content of the component.

[0164] In an embodiment, the glass article 100 made of the glass composition described above may have a thickness of 100 μm or less, preferably 20 μm to 100 μm, and may satisfy the following physical properties.

[0165] i) Thermal expansion coefficient: 90×10 -7 K -1 Up to 100×10 -7 K -1

[0166] ii) Glass transition temperature (Tg): 425 degrees Celsius (℃) to 525℃

[0167] iii) Density: 2.38 g / cm3 3 ) to 2.48g / cm 3

[0168] iv) Elastic modulus: 72 GPa to 82 GPa

[0169] v) Poisson's ratio: 0.20 to 0.22

[0170] vi) Hardness: 5.50 GPa to 6.50 GPa

[0171] vii) Fracture toughness: 0.75 MPa·m 0.5 ) to 0.85MPa·m 0.5

[0172] viii) Brittleness: 7.0 μm -0.5 Up to 8.0μm -0.5

[0173] ix) Surface roughness: 0.2nm to 0.4nm

[0174] Hereinafter, the embodiments will be described in more detail through manufacturing examples and experimental examples.

[0175] Manufacturing Example 1:

[0176] Preparation includes 65.15 mol% SiO 2 , 8.86 mol% Al 2 O 3 , 9.72 mol% Na 2 O, 3.20 mol% K 2 O, 10.08 mol% Li 2 The glass composition comprises 2.99 mol % of O and 2.99 mol % of MgO.

[0177] Comparative Example 1:

[0178] The glass composition is molded, cut, side-polished and tempered to form a glass product. Here, the first surface treatment and the second surface treatment are not performed.

[0179] Embodiment 1:

[0180] The glass product is manufactured by forming, cutting, side polishing, first surface treatment, tempering and second surface treatment using the glass composition. Here, the glass is immersed in a mixture including hydrofluoric acid (HF), sulfuric acid (H 2 SO 4 ) and ammonium fluoride (NH 4 F) or hydrofluoric acid (HF), sulfuric acid (H 2 SO 4 ) and ammonium fluoride (NH 4 F) The first surface treatment and the second surface treatment were performed at an etching rate of 0.29 μm / min. At this time, the total etching thickness of the glass article etched in the first surface treatment and the second surface treatment was 1 μm.

[0181] Embodiment 2:

[0182] A glass article was manufactured under the same conditions as in Example 1, except that the first surface treatment and the second surface treatment were performed at an etching rate of 0.65 μm / min.

[0183] Embodiment 3:

[0184] A glass article was manufactured under the same conditions as in Example 1, except that the first surface treatment and the second surface treatment were performed at an etching rate of 1.26 μm / min.

[0185] Embodiment 4:

[0186] In addition to immersing the glass in a solution containing hydrofluoric acid (HF), hydrochloric acid (HCl), and ammonium fluoride (NH 4 F) or hydrofluoric acid (HF), hydrochloric acid (HCl) and ammonium fluoride (NH 4 A glass article was manufactured under the same conditions as in Example 1 except that the first surface treatment and the second surface treatment were performed at an etching rate of 0.43 μm / min in a repair solution of composition F).

[0187] Embodiment 5:

[0188] A glass article was manufactured under the same conditions as in Example 4, except that the first surface treatment and the second surface treatment were performed at an etching rate of 0.74 μm / min.

[0189] Embodiment 6:

[0190] A glass article was manufactured under the same conditions as in Example 4, except that the first surface treatment and the second surface treatment were performed at an etching rate of 1.37 μm / min.

[0191] Experimental Example 1:

[0192] The glass products manufactured according to Comparative Example 1 and Examples 1, 2, 3, 4, 5 and 6 were prepared as 50 mm×50 mm specimens and the surface roughness was measured, and the results are shown in Figures 9 to 15 and are shown in Table 1 below.

[0193] For the surface roughness of the glass product, Nano Navi IIS-image model of SII Nano Technology Co., Ltd. was used. (The measurement mode was DFM, and the measurement range was 10 μm×10 μm)

[0194] Fig. 9 is a surface image of the glass product manufactured according to Comparative Example 1. Fig.10 is a surface image of the glass product manufactured according to Example 1. Fig.11 is a surface image of the glass product manufactured according to Example 2. Fig.12 is a surface image of the glass product manufactured according to Example 3. Fig.13 is a surface image of the glass product manufactured according to Example 4. Fig.14 is a surface image of the glass product manufactured according to Example 5. Fig.15 is a surface image of the glass product manufactured according to Example 6.

[0195] [Table 1]

[0196] Surface roughness(nm) Comparative Example 1 0.14 Example 1 0.44 Example 2 0.41 Example 3 0.40 Example 4 0.39 Example 5 0.35 Example 6 0.38

[0197] refer to Figures 9 to 15 and Table 1, the glass article not including or consisting of a surface treatment operation according to Comparative Example 1 exhibited a surface roughness of 0.14 nm, and the glass articles including or consisting of a surface treatment operation according to Examples 1 to 6 exhibited a surface roughness of approximately 0.35 nm to 0.44 nm.

[0198] Experimental Example 2:

[0199] In Example 1, Example 2 and Example 3, glass articles were manufactured by changing the total etching thickness of the first surface treatment and the second surface treatment to 3 μm, 5 μm and 10 μm. The results are shown together with Comparative Example 1. Fig.16 middle.

[0200] Fig.16 is a graph showing the surface roughness of glass articles manufactured according to Comparative Example 1 and Examples 1, 2, and 3 according to etching thickness.

[0201] refer to Fig.16 , even when the etching thickness of the first surface treatment and the second surface treatment increases, it is found that the surface roughness of the glass articles according to Examples 1 to 3 is in the range of about 0.35 nm to about 0.50 nm.

[0202] Experimental Example 3:

[0203] The glass product is manufactured by performing molding, cutting, side polishing, first surface treatment, tempering, and second surface treatment using the glass composition. Here, the glass is immersed in a solution including hydrofluoric acid (HF), sulfuric acid (H 2 SO 4 ) and ammonium fluoride (NH 4 F) or hydrofluoric acid (HF), sulfuric acid (H 2 SO 4 ) and ammonium fluoride (NH 4 F) to perform the first surface treatment and the second surface treatment. In addition, the first surface treatment was performed differently at an etching rate of 0.4 μm / min, 0.8 μm / min and 1.2 μm / min with a total etching thickness of 0.5 μm, 1.0 μm, 1.5 μm and 2.0 μm, respectively. The second surface treatment was equally performed at an etching rate of 1.2 μm / min with a total etching thickness of 0.5 μm.

[0204] A pen drop test ("PDT") was performed on the glass article according to Experimental Example 3, and the results are shown in Fig.17 middle. Fig.17 2 is a graph showing the PDT results of the glass article according to Experimental Example 3. Fig.18 A PDT device is schematically shown.

[0205] refer to Fig.18 , in PDT, a glass article UTG is attached to a polyethylene film PE by a pressure-sensitive adhesive PSA, and then fixed on a granite plate GP. After a pen PEN is fixed to the device by an electromagnet EM, a switch SW is operated to drop the pen PEN onto the glass article UTG. The pen PEN has a ball diameter of 0.7 mm and a weight of 5.35 g, and the drop height of the pen PEN is repeatedly changed by 0.1 cm within a range of 0.5 cm to 10 cm. When the pen PEN is repeatedly dropped, the drop height of the pen PEN is measured when a break finally occurs.

[0206] refer to Fig.17 , it was confirmed that as the etching rate and etching thickness of the first surface treatment increased, the drop height of the pen at which cracks occurred in the glass article generally increased.

[0207] Experimental Example 4:

[0208] According to the following Table 2, glass articles according to Comparative Example 2 and Example 7 were prepared, and the glass article manufacturing process was performed. In Example 1 described above, in the glass article manufacturing process, the first surface treatment was performed at an etching rate of 1.2 μm / min and an etching thickness of 1.0 μm, and the second surface treatment was performed at an etching rate of 1.2 μm / min and an etching thickness of 0.5 μm.

[0209] The components and ingredient ratios of the glass articles according to Comparative Example 2 and Example 7 are shown in Table 2 below. In addition, the density, glass transition temperature, hardness, fracture toughness, brittleness, elastic modulus, thermal expansion coefficient, and Poisson's ratio of the glass articles according to Comparative Example 2 and Example 7 were measured and shown in Table 3 below.

[0210] Here, the glass transition temperature (Tg) was examined using a differential thermal analysis ("DTA") apparatus by preparing 5 grams (g) of each glass composition and raising the temperature to the glass transition temperature range at a rate of 10 Kelvin / minute (K / min). The thermal expansion coefficient was examined using a thermomechanical analyzer ("TMA") by preparing a specimen having a size of 10 mm×10 mm×13 mm for each glass composition and raising the temperature to the glass transition temperature range at a rate of 10 K / min.

[0211] The elastic modulus and Poisson's ratio were examined using an elastic modulus tester by preparing a specimen having a size of 10 mm×20 mm×3 mm for each glass composition and examining the stress and strain of the specimen.

[0212] The hardness and fracture toughness were calculated using the following equations (3) and (4) by applying a load of 4.9 Newtons (N) for 30 seconds with a Vickers hardness tester using a 19 μm-sized diamond tip.

[0213]

[0214] Among them, H V is the Vickers hardness, F is the load, and a is the indentation length.

[0215]

[0216] Where K IC is the fracture toughness, φ is the constraint value (φ≈3), H V is the Vickers hardness, K is a constant (K=3.2), a is the indentation length, and c is the crack length.

[0217] The brittleness was calculated using the following equation (5) by applying a load of 4.9 N for 30 seconds using a Vickers hardness tester.

[0218]

[0219] Among them, B is brittleness, which is a constant (2.39N 1 / 4 / μm 1 / 2 ), P is the indentation load, a is the indentation length, and C is the crack length.

[0220] [Table 2]

[0221]

[0222] [Table 3]

[0223]

[0224]

[0225] Referring to Table 2 and Table 3 above, it can be seen that Example 7 has a higher elastic modulus than Comparative Example 2. The elastic modulus may mean excellent flexibility.

[0226] In addition, it can be seen that Example 7 has higher fracture toughness than Comparative Example 2. Fracture toughness may mean excellent impact resistance.

[0227] Experimental Example 5:

[0228] PDT was performed on the glass articles according to Comparative Example 2 and Example 7, and the results are shown in Fig.19 middle.

[0229] Fig.19is a graph showing PDT results of glass articles according to Comparative Example 2 and Example 7.

[0230] refer to Fig.19 , the glass product according to Comparative Example 2 was broken when the pen was dropped at a height of about 4 cm, but the glass product according to Example 7 was broken when the pen was dropped at a height of about 7 cm, indicating that the glass product was broken when the pen was dropped at a higher height.

[0231] Therefore, it can be seen that the glass article according to Example 7 has excellent impact resistance.

[0232] In summarizing the detailed description, those skilled in the art will appreciate that many changes and modifications may be made to the preferred embodiments without departing substantially from the principles of the present invention. Therefore, the preferred embodiments of the present invention disclosed are used in a general and descriptive sense only and not for the purpose of limitation.

Claims

1. A glass product, wherein: The glass product comprises: A glass composition comprising 60 mol% to 70 mol% of SiO2, 5 mol% to 15 mol% of Al2O3, 5 mol% to 15 mol% of Na2O, greater than 0 mol% and equal to or less than 5 mol% of K2O, 5 mol% to 15 mol% of Li2O, and greater than 0 mol% and equal to or less than 5 mol% of MgO based on the total amount, and the glass composition satisfies the following Relationship 1: 0.1≤Al2O3 / (the sum of Na2O, K2O and Li2O)≤0.7 Relationship 1, Wherein, Al2O3, Na2O, K2O and Li2O in Relational Formula 1 indicate the molar percentage contents of Al2O3, Na2O, K2O and Li2O in the glass composition, respectively, and Wherein, the glass article has a thickness of 100 μm or less.

2. The glass product according to claim 1, in, The glass article has a thickness in the range of 20 μm to 100 μm.

3. The glass product according to claim 1, in, The thermal expansion coefficient of the glass product is 90×10 -7 K -1 Up to 100×10 -7 K -1 within the range.

4. The glass product according to claim 1, in, The glass article has a glass transition temperature in the range of 425°C to 525°C.

5. The glass product according to claim 1, in, The density of the glass product is 2.38 g / cm 3 Up to 2.48g / cm 3 within the range.

6. The glass product according to claim 1, in, The glass article has an elastic modulus in a range of 72 GPa to 82 GPa.

7. The glass product according to claim 1, in, The glass article has a Poisson's ratio in the range of 0.20 to 0.

22.

8. The glass product according to claim 1, in, The hardness of the glass article is in the range of 5.50 GPa to 6.50 GPa.

9. The glass product according to claim 1, in, The fracture toughness of the glass product is 0.75 MPa·m 0.5 To 0.85MPa·m 0.5 within the range.

10. The glass product according to claim 1, in, The brittleness of the glass product is 7.0 μm -0.5 Up to 8.0μm -0.5 within the range.

11. The glass product according to claim 1, in, The surface roughness of the glass article is in the range of 0.2 nm to 0.45 nm.

12. The glass product according to claim 1, in, The glass product is a foldable glass product.

13. A glass composition, wherein: The glass composition includes 60 mol% to 70 mol% of SiO2, 5 mol% to 15 mol% of Al2O3, 5 mol% to 15 mol% of Na2O, greater than 0 mol% and equal to or less than 5 mol% of K2O, 5 mol% to 15 mol% of Li2O, and greater than 0 mol% and equal to or less than 5 mol% of MgO based on the total amount, and the glass composition satisfies the following Relationship 1: 0.1≤Al2O3 / (the sum of Na2O, K2O and Li2O)≤0.7 Relationship 1, Wherein, Al2O3, Na2O, K2O and Li2O in Relationship 1 indicate the molar percentage contents of Al2O3, Na2O, K2O and Li2O in the glass composition, respectively.

14. A display device, wherein: The display device comprises: A display panel including a plurality of pixels; a cover window, disposed on the display panel; and an optically transparent bonding layer disposed between the display panel and the cover window, Wherein, the cover window comprises: A glass composition comprising 60 mol% to 70 mol% of SiO2, 5 mol% to 15 mol% of Al2O3, 5 mol% to 15 mol% of Na2O, greater than 0 mol% and equal to or less than 5 mol% of K2O, 5 mol% to 15 mol% of Li2O, and greater than 0 mol% and equal to or less than 5 mol% of MgO based on the total amount, and the glass composition satisfies the following Relationship 1: 0.1≤Al2O3 / (the sum of Na2O, K2O and Li2O)≤0.7 Relationship 1, Wherein, Al2O3, Na2O, K2O and Li2O in the relational formula 1 indicate the molar percentage contents of Al2O3, Na2O, K2O and Li2O in the glass composition, respectively, and The cover window has a thickness of 100 μm or less.

15. The display device according to claim 14, in, The cover window has a thickness of 20 μm to 100 μm.

16. The display device according to claim 14, in, The cover window has a 90×10 -7 K -1 Up to 100×10 -7 K -1 The coefficient of thermal expansion.

17. The display device according to claim 14, in, The cover window has a glass transition temperature of 425°C to 525°C.

18. The display device according to claim 14, in, The cover window has a thickness of 2.38 g / cm 3 Up to 2.48g / cm 3 density.

19. The display device according to claim 14, in, The cover window has an elastic modulus of 72 GPa to 82 GPa.

20. The display device according to claim 14, in, The cover window has a Poisson's ratio of 0.20 to 0.

22.

21. The display device according to claim 14, in, The cover window has a hardness of 5.50 GPa to 6.50 GPa.

22. The display device according to claim 14, in, The cover window has a 0.75 MPa·m 0.5 To 0.85MPa·m 0.5 fracture toughness.

23. The display device according to claim 14, in, The cover window has a 7.0 μm -0.5 Up to 8.0μm -0.5 brittleness.

24. The display device according to claim 14, in, The cover window has a surface roughness of 0.2 nm to 0.45 nm.

25. The display device according to claim 14, in, The display device is a foldable display device.

26. A method of manufacturing a glass product, wherein: The method comprises: forming the glass composition into glass having a plate shape; cutting the glass; performing a first surface treatment on the glass; Tempering the glass; and performing a second surface treatment on the glass, The glass composition includes 60 mol% to 70 mol% of SiO2, 5 mol% to 15 mol% of Al2O3, 5 mol% to 15 mol% of Na2O, greater than 0 mol% and equal to or less than 5 mol% of K2O, 5 mol% to 15 mol% of Li2O, and greater than 0 mol% and equal to or less than 5 mol% of MgO based on the total amount, and the glass composition satisfies the following Relationship 1: 0.1≤Al2O3 / (the sum of Na2O, K2O and Li2O)≤0.7 Relationship 1 Wherein, Al2O3, Na2O, K2O and Li2O in Relationship 1 indicate the molar percentage contents of Al2O3, Na2O, K2O and Li2O in the glass composition, respectively.

27. The method according to claim 26, in, The first surface treatment etches the surface of the glass at an etching rate of 1 μm / min to 1.4 μm / min.

28. The method according to claim 26, in, The first surface treatment etches the surface of the glass to a thickness of 0.8 μm to 1.2 μm.

29. The method according to claim 26, in, The second surface treatment etches the surface of the glass at an etching rate of 1 μm / min to 1.4 μm / min.

30. The method according to claim 29, in, The second surface treatment etches the surface of the glass to a thickness of 0.2 μm to 0.8 μm.

31. The method according to claim 26, in, After the second surface treatment, the surface roughness of the glass is in the range of 0.2 nm to 0.4 nm.